Towards a Semantic-Aware Collaborative Working Environment - Martínez Carreras, María A.; Marín Pérez, Juan M.; Bernal Bernabé, Jorge; Alcaraz Calero, José M.; Martínez Pérez, Gregorio; Gómez Skarmeta, Antonio F. (COMPUTING AND INFORMATICS, 2013)
Collaborative Working Environments (CWEs) enable an efficient collaboration between professionals, specially those settled in different locations of a company or stakeholders from different companies. This can be of great help for small and medium enterprises (SMEs), as an effective way to share information. However, it can be difficult for SMEs to have access to a fully integrated CWE providing different tools (e.g., videoconferencing, instant messaging, etc.). Currently, they may define a CWE as a combination of heterogeneous and non-integrated tools which are not able to share information between them. An integrated CWE would provide SMEs with the necessary means to collaborate, making information exchange easier.